Research on the relationship between serum indoxyl sulfate concentration and iron dynamics index in patients with end-stage kidney disease: a cross-sectional study - Takuya Yoshida; Masayuki Tsujimoto; Sachiyo Kawakami; Haruno Fujioka; Yuko Irie; Saki Nakatani; Ayako Iso; Ayaka Sugiyama; Mizuho Miyake; Kazumi Hirato; Rie Tanaka; Tomoko Oda; et al. (Renal Replacement Therapy, 2022)
Abstract Background Chronic kidney disease (CKD) is frequently associated with renal anemia. Erythropoiesis-stimulating agent-hyporesponsive anemia is often caused by iron deficiency in patients with CKD. We hypothesized that high accumulation of indoxyl sulfate, a uremic toxin, accelerates iron deficiency in patients with CKD. The aim of this study was to clarify whether the accumulation of indoxyl sulfate is a cause of iron deficiency in patients with CKD. Therefore, we investigated the association between serum indoxyl sulfate concentration and iron dynamics in patients with end-stage kidney disease (ESKD). Methods We performed a cross-sectional study on 37 non-dialyzed patients with ESKD, who were hospitalized to undergo maintenance hemodialysis treatment at Shirasagi Hospital. Serum indoxyl sulfate concentration, iron dynamics parameters and other laboratory data were measured immediately before the initiation of hemodialysis treatment. Clinical characteristics were obtained from electronic medical records. Results The estimated glomerular filtration rate (eGFR) of 37 patients with ESKD was 5.08 (3.78–7.97) mL/min/1.73 m2 (median [range]). Serum ferritin and transferrin saturation (TSAT) were 90 (10–419) ng/mL and 20 (8–59)% (median [range]), respectively. Serum indoxyl sulfate concentration was 62 (11–182) μM (median [range]). Serum indoxyl sulfate concentration was inversely correlated with serum ferritin level (ρ = − 0.422, p = 0.011), but not with TSAT, age, gender, eGFR and c-reactive protein (CRP) in 37 patients. In eight patients taking iron-containing agents, serum indoxyl sulfate concentration was strongly correlated with serum ferritin level (ρ = − 0.796, p = 0.037); however, in 29 patients not taking an iron-containing agent, this correlation was not observed (ρ = − 0.336, p = 0.076). In the multivariate analysis including age, gender, eGFR and CRP, the correlation between serum indoxyl sulfate concentration tended to be, but not significantly correlated with serum ferritin level in 37 patients (regression coefficient = − 54.343, p = 0.137). Conclusion Our study suggests that serum accumulation of indoxyl sulfate is one of causes not to increase serum ferritin level in patients with ESKD taking an iron-containing agent. Further clinical study is needed to reveal the appreciable relationship between serum ferritin and serum indoxyl sulfate.